In Vitro Mass Propagation of Heliotropium indicum L., using Apical and Axillary Bud Explants - Hassan, AKM Sayeed; Begum, Nadira; Jahan, Miskat Ara Akhter; Khatun, Rahima (Bangladesh Journal of Scientific and Industrial Research, 2010)
A consequency was obtained for mass propagation of a valuable ayurvedic medicinal herb, Heliotropium indicum Linn. (Boraginaceae) through in vitro culture. Apical and axillary buds of young sprouts from selected plants were used as explants. Best shoot induction was observed on MS basal medium supplemented with 0.5 mg/l BAP + 0.1 mg/l GA3, in which 92% of the axillary buds explants produced 12 shoots per culture. Repeated subcultures in the same medium, resulted rapid shoot multiplication with 18 shoots per culture. In vitro raised shoots rooted on half strength MS medium with 0.5 mg/l IBA. For acclimatization and transplantation, the plantlets in the rooting culture tubes were kept in normal room temperature for 7 days before transplanting in pots where plantlets were reared for three weeks. The survival rate of regenerated plantlets was 85%. Key words: Heliotropium indicum; Medicinal plant; Shoot proliferation; Micropropagation; Acclimatization. DOI: 10.3329/bjsir.v45i1.5185 Bangladesh J. Sci. Ind. Res. 45(1), 69-74, 2010